Kinetics of Aquation of Tris(oxalato)chromate(III) and Tris(malonato)chromate(III) from Sulfuric Acid Solutions: A Solvent Extraction Study - Subba Rao Mushini, Venkata; Ananta Ramam, V.; Muralidhara Rao, V. (Asian Journal of Chemistry, 2010)
The kinetics of aquation of tris(oxalato)chromate(III) and tris(malonato)chromate(III) anions have been studied by the solvent extraction technique. Trilaurylamine is used as an extractant. The extraction of these complex species is carried out using trilaurylamine in chloroform as extractant with appropriate concentrations of sulfuric acid in the aqueous phase. The observed first order rate constants are found to depend on the H+ concentration. Rate constants are determined by using KINTOB software procedure. The activation parameters are calculated. The spectra of tris(oxalato)chromate(III) and tris(malonato)chromate(III) in aqueous phase are recorded as a function of standing time, in order to understand the formed product species. The product species are identified as mixture of species [Cr(Ox)2(H2O)2]–, [Cr(Ox)(H2O)4]+ and Cr(H2O)6 3+ in the case of tris(oxalato)chromate(III) and [Cr(mal)2(H2O)2]– and Cr(H2O)63+ in case of tris(malonato)chromate(III).